Shahid's Effort To Integrate Into Group Of Fundamentalist Moslem In The Black Album Novel By Hanif Kureishi(1995):An Individual Psychological Approach - Nugroho, Dwi, Drs. Abdillah Nugroho, M. Hum, Siti Fatimah, S.Pd. M. Hum (2013)
This study is about Shahid's Effort to Integrate into Group of Fundamentalist Moslem in The Black Album novel by Hanif Kureishi by using individual pscychological approach. It is done by establishing two objectives: the first analyzes the novel based on the structural elements of the novel and the second discribes Shahid's Effort to Integrate into Group of Fundamentalist Moslem based on individual pscychological Approach. This study uses qualitative research, in this method the researcher uses two data source, namely primary and secondary. Primary data source is the data of the novel, secondary data source is references and materials related to the study picking up from the books or internet, and other data which deal with the research. Both data are collected by conducting library research and analyzed by descriptive analysis. The results of this study are as follows: based on the structural analysis of each element, it shows that the character and characterization, setting, plot, point of view, theme is supporting each other to produce a good quality novel. Then, based on the individual psychology analysis, the study shows that the problem faced by the major character is her own psychology condition to decide the appropriate ways for her life. This novel also shows the process how the resilience to stay alive will produce the amazing result.